Chemical reduction of graphene oxide using green reductants. (August 2017) - De Silva, K.K.H.; Huang, H.-H.; Joshi, R.K.; Yoshimura, M.
Abstract: Graphene has exceptional physical, chemical, mechanical, thermal and optical properties which offer huge potential for applications in various sectors. Chemical oxidation of graphite to graphene oxide followed by the reduction process is the commonly used method for mass scale production of graphene or reduced graphene oxide (RGO). Among the large number of chemical reducing agents used to prepare RGO or graphene, the most efficient reductant is hydrazine. It is toxic in nature and harmful to the environment, thus it is in high demand to use green reductants for RGO synthesis. We understand that due to high demand of graphene/graphene oxide/reduced graphene oxide recently and which is expected to be more in future, green synthesis methods are extremely important. In this article, we have studied the synthesis methods, characterization and the possible mechanism for green reduction, especially by ascorbic acid. This article could possibly motivate the researcher worldwide to innovate new green methods for mass scale production of graphene based materials. Graphical abstract: